Three new species of Proparachaeta Townsend, 1928 (Diptera: Tachinidae) from Brazil and Peru, and redescription of the type species from Paraguay - Toma, Ronaldo (Instituto de Ecología, A.C., 2019)
Four species of Proparachaeta Townsend (Goniini) are recognized in the Neotropical Region: the type species P. paraguayensis Townsend, 1928, from Paraguay, Proparachaeta niheii sp. n. from Brazil, Proparachaeta punensis sp. n. from Peru and Proparachaeta rondonensis sp. n. from Brazil. The type species is redescribed and the three new species are described and illustrated. A key is provided for the identification of the four species.